2011
DOI: 10.1016/j.virusres.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Infection of cultured bovine cells with bovine herpesvirus 1 (BHV-1) or Sendai virus induces different beta interferon subtypes

Abstract: In contrast to mice or humans, cattle contain three beta interferon (IFN-β) genes with distinct transcriptional promoters suggesting IFN-β gene expression is not stimulated the same by different viruses. To test this hypothesis, we compared expression of the three IFN-β subtypes after infection with a RNA virus, Sendai, versus a large DNA virus, bovine herpesvirus 1 (BHV-1). Infection of low passage bovine kidney (BK) or established bovine kidney cells (CRIB) with Sendai virus has consistently led to high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 50 publications
(59 reference statements)
3
40
0
Order By: Relevance
“…IFN-␤2 RNA levels were increased 3.5-fold at 8 h after infection, whereas a modest 2-fold increase was detected at 4 h after infection with wt BHV-1. Treatment with CHX led to higher levels of IFN-␤1 and IFN-␤2 mRNA by 4 h after infection with the LR mutant virus or wt BHV-1, which was consistent with a previous study (16). These studies demonstrated that IFN-␤1 RNA levels were readily detected in low-passage-number bovine cells following infection with the LR mutant virus but not with wt BHV-1.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…IFN-␤2 RNA levels were increased 3.5-fold at 8 h after infection, whereas a modest 2-fold increase was detected at 4 h after infection with wt BHV-1. Treatment with CHX led to higher levels of IFN-␤1 and IFN-␤2 mRNA by 4 h after infection with the LR mutant virus or wt BHV-1, which was consistent with a previous study (16). These studies demonstrated that IFN-␤1 RNA levels were readily detected in low-passage-number bovine cells following infection with the LR mutant virus but not with wt BHV-1.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to humans or mice, cattle contain three IFN-␤ genes (IFN-␤1, IFN-␤2, and IFN-␤3) that are regulated by distinct promoters (16,80,82). BHV-1 infection increases IFN-␤1 and IFN-␤3 RNA levels in established bovine cell lines (16,59) but not in low-passage-number bovine cells (16). When de novo protein synthesis is inhibited by cycloheximide (CHX) treatment, infection of low-passagenumber bovine cells with BHV-1 leads to increased IFN-␤1, but not IFN-␤3, RNA levels (16).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations